Pengaruh Penerapan Gaya Mengajar Inklusi Terhadap Penguasaan Gerak Dasar Pada Spike Dalam Permainan Bola Voli Pada Peserta Didik SMK Negeri 1 Tomohon - Kalvarius Niatman Gea; Nolfie Piri; Tony Pandaleke (STIKES Columbia Asia Medan, 2025)
Education is the process of forming and developing individual character through learning activities. Education can also be considered a provision given to someone that will be useful in the future or when they are adults. Volleyball is one of the most popular sports in the community because it is affordable and can be played anywhere. after making observations in the field, it turns out that there are many students who do not understand and understand the lessons with this method. this is evident from the report card grades of physical education students, many of whom still do not reach the standard score or KKN (75) and it is also evident when researchers make observations when teachers teach many students who do not understand and have difficulty doing a movement. The method used in this research is the experimental method and the sample used in this study were students of SMK Negeri 1 Tomohon totaling 34 students and divided into two groups, namely the experimental group of 17 students and the control group of 17 students. The research design used was Randomized Pre-test and Post-test Control Group Desing. The instrument used is the Basic Gear Mastery Test on Spike in Volleyball Games. The conclusion in this study is that the application of the inclusion style has an influence on improving basic movements on spikes in volleyball games for students of SMK NEGERI 1 TOMOHON.